Las entidades solidarias y su tributación (2012)
The cooperative institutes are legal entities in the development of their activities are characterized by social work to make people within it. This social work thrives in these institutions prevails over the individual interest in such a way that encourages the creation of employment, education resources available to its partners and generate a greater chance of competition with their involvement in the trade. The Government recognizes the benefits to the community and therefore supports the growth and strengthening of these forms of association through some tax privileges.